Tax Planning sebagai Instrumen Efisiensi Pajak Penghasilan Badan: Studi pada PT Selamat Sempurna Tbk - Mikanti Annisa Sugrining Rahayu; Ida Farida Adi Prawira; Memen Kustiawan (Jurnal Ilmiah Wahana Pendidikan, 2026)
This study aims to analyze tax planning strategies as an effort to optimize Corporate Income Tax (PPh) payments at PT Selamat Sempurna Tbk, a leading automotive component manufacturer in Indonesia. Employing a descriptive method with a qualitative approach and secondary data from the 2023–2024 financial statements, this research identifies accounts that historically generate positive fiscal corrections, specifically employee welfare costs, donations and gifts, and miscellaneous accounts. Tax planning strategies were implemented by converting non-deductible expenses into deductible expenses. The analysis results indicate that the implementation of tax planning successfully reduced income tax expenses by Rp1,995 million in 2024 and Rp1,614 million in 2023, while significantly improving the company's fiscal profit efficiency. This study demonstrates that systematic and regulation-based tax planning enables companies to legally minimize tax burdens, enhance financial efficiency, and maintain tax compliance without violating applicable regulations.